Iron-doped boron nitride nanocage for targeted delivery of 5 fluorouracil: A DFT guided experimental study with in vitro validation - Sandi, Sara; Shameli, Abolghasem; Noei, Maziar; Balali, Ebrahim; Mirzaei, Mahmoud (Archives of Advances in Biosciences, 2026)
Background and Aim: 5-Fluorouracil (5-FU) is a widely used anticancer drug but suffers from severe systemic toxicity, short half-life, and low tumor selectivity. Boron nitride nanocages have emerged as promising drug delivery vehicles due to their high biocompatibility and low cytotoxicity. Transition metal doping, particularly with iron, can enhance drug binding affinity through electronic effects. The purpose of this study was to evaluate the potential of iron-doped boron nitride nanocage (NC Fe) as a nanocarrier for targeted delivery of 5-FU using a multiscale approach combining DFT calculations, experimental adsorption studies, and in vitro cellular/molecular assays. Methods: DFT calculations at the B3LYP/6 31G(d) level were performed to determine the interaction energy, QTAIM parameters, NBO charge transfer, and HOMO LUMO gap of the FU-NC-Fe complex. Batch adsorption experiments were conducted to optimize pH, contact time, initial drug concentration, and adsorbent dosage. MTT assay, flow cytometry (Annexin V FITC/PI staining), and qRT-PCR (Bax and Bcl-2 expression) were performed on MCF-7 breast cancer cells and normal HFF fibroblasts. Results: DFT calculations revealed a negative interaction energy of –59.8 kJ/mol with positive ∇²ρ(r) (0.098 a.u.), confirming spontaneous noncovalent binding. Bidirectional charge transfer of 0.29 electrons and an 11.8% reduction in HOMO LUMO gap were observed. Optimal adsorption conditions (pH 7.0, 30 min, 20 mg/L, 0.10 g NC Fe) yielded 76.5% adsorption efficiency. FU-NC-Fe exhibited significantly enhanced cytotoxicity against MCF- 7 cells (IC₅₀ = 8.7 µg/mL) compared to free 5-FU (18.4 µg/mL), with a selectivity index of 4.86. The complex induced 52.7% total apoptosis (vs. 28.4% for free drug) and increased the Bax/Bcl-2 ratio 4.5 fold (21.3 vs. 4.7). Pristine NC-Fe showed excellent biocompatibility (IC₅₀ > 200 µg/mL). Conclusion: Iron-doped boron nitride nanocage is a highly promising nanocarrier for targeted 5-FU delivery, offering enhanced anticancer efficacy, high cancer cell selectivity, and potent apoptosis induction through the mitochondrial pathway.